Historical antecedents of /h/, /s/, /j/ and /ř/ in Utkuhiksalik (Inuktitut) - Dyck, Carrie; Briggs, Jean (Études/Inuit/Studies, 2005)
AbstractUtkuhiksalik is a sub-dialect of Natsilik within the Western Canadian Inuit dialect continuum. Unlike many Western dialects, Utkuhiksalik contrasts /h/ and /s/, /j/ and /ř/. The goal of this paper is to show how such contrasts arose: we describe the sound changes from Proto-Eskimoan *j, *ð, and *c to Utkuhiksalik /h/, /s/, /j/ and /ř/.